What Can Western Medicine Relearn from Chinese Medicine? - Peter Emanuel Petros (Wolters Kluwer Health/LWW, 2020)
The article begins with a short review of similarities between traditional Chinese medicine (TCM) and original Hippocratic medicine. Both were holistic, and taking every aspect contributing to illness into account, both followed the dictum, "first do no harm." A key difference between the two, even 2400 years ago, was the Hippocratic emphasis on scientific medicine. The explosion of science and technology in the latter half of the 2nd century was applied to Western medicine, which became ever more complex, specialized, and reductionist, losing much of its original holism. The strength of TCM is its holistic approach and techniques such as acupuncture, so necessary for the management for patients who have chronic illnesses such as pain for which Western medicine has few answers.